Xeno-free generation of new Yazd human embryonic stem cell lines (Yazd4-7) as a prior stage toward good manufacturing practice of clinical-grade raw materials from discarded embryos: A lab resources report - Fatemeh Hajizadeh-Tafti; Jalal Golzadeh; Fatemeh Akyash; Somayyeh-Sadat Tahajjodi; Ehsan Farashahi-Yazd; Hassan Heidarian-Meimandi; Behrouz Aflatoonian (International Journal of Reproductive BioMedicine, 2023)
Abstract Background: Xeno-free generation of human embryonic stem cells (hESCs) is important to prevent potential animal contaminations in culture for advanced cell-based therapeutic applications. Xeno-free production of hESCs is the first step for manufacturing clinical-grade hESC lines. Objective: To produce new hESC lines in xeno-free condition. Materials and Methods: This lab resources report was conducted at Stem Cell Biology Research Center, Yazd, Iran from 2019-2022. 4 new hESC lines from 11 (10 fresh and 1 frozen) donated surplus discarded human embryos were established. In this study, we report the xeno-free derivation of new Yazd hESC lines (Yazd4-7), without using immunosurgery, by culturing intact zona-free blastocysts obtained from discarded embryos onto the YhFF#8 cells as a feeder layer in a microdrop culture system. The pluripotency gene expression profile of the cell lines was assessed by reverse transcription polymerase chain reaction and the expression of specific surface markers was detected using immunofluorescent staining. In vitro differentiation was induced using embryoid body formation and gene expression profile of 3 germ layers and germ cells. Reverse transcriptase polymerase chain reaction was investigated to prove their pluripotent capacity. Results: In sum, we have been able to generate 4 new hESC lines (Yazd4-7) from 11 discarded embryos in xeno-free culture conditions using a micro drop culture system and YhFF#8 as a human source feeder layer. Conclusion: The outcome of this work can be the foundation for the future allogeneic cell-based therapeutic application using clinical grade good manufacturing practice-derived hESC derivatives.